2015
DOI: 10.1186/s12886-015-0031-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between retinal vein occlusion, axial length and vitreous chamber depth measured by optical low coherence reflectometry

Abstract: BackgroundResults of ocular biometric measurements in retinal vein occlusion (RVO) eyes are still inconclusive and controversial. The aim of this study was to evaluate the association between ocular axial length (AL), vitreous chamber depth (VCD) and both central (CRVO) and branch retinal vein occlusions (BRVO) using optical low coherence reflectometry (OLCR).MethodsBoth eyes of 37 patients with unilateral CRVO (mean age: 66 ± 14 years, male:female - 21:16) and 46 patients with unilateral BRVO (mean age: 63 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…We found a correlation between optic disc dimension and axial length, in agreement with results of Miglior et al (16). Consistent with Bandello et al (17), we found no significant difference in axial length compared with controls; other studies reported a shorter axial length in eyes with CRVO (18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
“…We found a correlation between optic disc dimension and axial length, in agreement with results of Miglior et al (16). Consistent with Bandello et al (17), we found no significant difference in axial length compared with controls; other studies reported a shorter axial length in eyes with CRVO (18)(19)(20).…”
Section: Discussionsupporting
confidence: 92%
“…Having identified a mechanism to modulate axial growth holds promise for hyperopes, and provides a platform for an extension to this work. The ability to accelerate axial growth in hyperopes may help to decrease the risk of ocular comorbidities associated with small globes 6 , 7 , 8 , 9 as well as reduce the burden of refractive error in these children. 1 , 2 , 3 , 4 , 5 Furthermore, multifocal contact lenses in children with hyperopia appear to be well tolerated both from a handling and wearing perspective as well as providing good visual performance.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike myopia, and despite the known visual consequences 1 , 2 , 3 , 4 , 5 and pathological implications of hyperopia, 6 , 7 , 8 , 9 there has been inertia to address the modulation of refractive error in hyperopic individuals. Hyperopia occurs as a consequence of insufficient ocular growth and a failure to emmetropise in childhood, with the majority of hyperopic refractive errors resulting from an eye that is too short for its refractive power.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, axial length, low anterior chamber depth, and hypermetropic refraction error were found in patients with hypertension. The short axial length causes the scleral canal to be smaller and the passing vessel structures pass through a narrower area (17). The results show that there is an increased risk of retinal vein occlusion in eyes with narrow anterior chamber (18)(19), short axial length (20)(21) and hyperopia (22-23) in various studies.…”
Section: Discussionmentioning
confidence: 82%